Leadership Attributes Among Women Bankers - Kumar, Harish (International Journal of Psychosocial Rehabilitation, 2019)
Women make up a disproportionately small percentage of executive boards at banks and financial oversight organizations. Less than 20% of board positions in banks and financial oversight organizations are held by women across the world. In contrast, there is a sizable pool of qualified female graduates. In the United States and the United Kingdom, women accounted for half of all business and social science graduates in 2010-2011, but just 30% of all economics graduates. A "glass ceiling" in finance is becoming more evident, yet it may not have much of an effect on financial outcomes like stability. Existing research is patchy, with studies focused on either narrow characteristics of risk-taking or narrow geographical regions. This paper compiles a large dataset on the banking industry, including its features and performance, and also on the proportion of women on the boards of trustees from various sources, covering 72 nations over 13 years, in order to investigate the correlation between gender and financial security. The study also introduces a new dataset on the percentage of women serving on banking supervisory agency boards in 113 countries to investigate whether or not the presence of women on such boards correlates with certain banking outcomes, like stability. Our research adds to the scholarly conversation in two ways. In the first place, we provide extensive data that enables us to give fresh stylized statistics on the proportion of women serving on bank boards and in managerial positions across different banking sectors and geographies. Women make up fewer than 2% of CEOs in the banking industry, as shown by the sample, which also confirms the low representation of women on boards. When comparing savings banks to investment banks, holding companies for banks, and insurance companies, the former has a larger percentage of women working there. Our data challenges conventional wisdom by revealing that women make up a disproportionately large proportion of bank board members and banking supervisory agency board members in several low- and middle-income nations. Second, the article discovers fresh data indicating that the presence of women on boards of banks may have an impact on bank stability through larger capital buffers, while other important characteristics are held constant. There seems to be a correlation between the number of women on banking oversight boards and the health of financial institutions